Edukasi Akad-Akad Keuangan Syariah Pada Mahasiswa Stai Al-Hikmah Medan - Tampubolon, Rhoni Ilham; S, Susianto; Nasution, Surayya Fadhilah; Khairiyah, Ririn (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service is carried out for students of STAI Al-Hikmah Medan. The purpose of this community service is to determine the level of understanding of STAI Al-Hikmah Medan students about education of sharia financing contracts and to determine the level of success of this Community Service (PKM) activity. The methods used in this Community Service (PKM) activity are through counseling, presentations and discussions. The results of the service show that the Community Service (PKM) program for STAI Al-Hikmah Medan students can be organized well and run smoothly according to the activity plan that has been prepared. The results of this service conclude that first, STAI Al-Hikmah Medan students have a diverse understanding of sharia financial transactions, some already understand, some are still hesitant, and some do not understand. Second, the achievement of the objectives of the STAI Al-Hikmah Medan student PKM activity program has been carried out in collaboration between students and community service where it is in accordance with the rundown of the event and the time that has been determined previously